Accountability and Learning: Exploding the Myth of Incompatibility between Accountability and Learning - and Guijt, Irene (NGO Management, 2010)
When accountability is understood as reporting on pre-deined deliverables, it is often considered to be irreconcilable with learning. This conventional wisdom inhibits an appreciation of their connection. In this chapter, Irene Guijt exposes the laws and traps in reasoning that keep accountability and learning apart. She provides practitioners with principles and basic good ideas that open up prospects for accountability and learning to complement each other.